The mediating effect of proactive knowledge sharing among transformational leadership, cohesion, and learning goal orientation on employee performance - Layaman Layaman; Pahlawansjah Harahap; Indi Djastuti; Aan Jaelani; Diana Djuwita (Business: Theory and Practice, 2021)
The background of this study is based on the controversial relationship between transformational leadership and employee performance. Empirical and theoretical models resolve the controversy by building a new concept based on proactive knowledge sharing. The study established the influence of transformational leadership, cohesion and learning goal orientation on proactive knowledge sharing and employee performance. A total of 7 hypotheses were developed to solve the study problem, while purposive sampling was used in data collection. The respondents consisted of 6 employees of Sharia Banking in Indonesia. The SEM results indicate that five hypotheses were significant, while 2 were insignificant. Furthermore, proactive knowledge sharing strongly mediates the relationship between the studied variables. These results confirm the withdrawal of the new concept in improving employee performance.